The Chinese "Oppression" Remedy: Creative Interpretations of Company Law by Chinese Courts. (1st July 2015) - Hawes, Colin; Lau, Alex K.L.; Young, Angus
Abstract: This is the first detailed study of the Chinese oppression remedy under the PRC Company Law (article 20.1-2). Compared to its U.K., Canadian, and Australian equivalents, the wording of the Chinese remedy is vague, and the Supreme People's Court has not clarified its meaning. Legal scholars have virtually ignored this remedy due to its vagueness and apparent unenforceability, and the Supreme People's Court has not produced any authoritative interpretations to clarify its meaning. Yet Chinese courts have acted pragmatically, building up a body of de facto case precedents to transform this remedy into an effective tool for minority shareholders, both Chinese and foreign (and in some cases companies too), to obtain redress for a broad range of wrongs committed by abusive shareholders. At the same time, the vagueness of the statute has led courts to draw differing conclusions over issues such as who is a proper plaintiff; how the oppression remedy relates to the derivative action; and how the term "shareholder" should be defined. These differences need to be addressed by the Supreme People's Court or by legislative amendment to avoid further inconsistent outcomes for parties involved in intra-corporate disputes in China. Alternatively, the use of case precedents based on online judgment databases should be formalized in China to bring more predictability to statutory interpretation and more consistency among courts throughout the country.